Analysis Of The Use Of Phrases In The Short Story "The Cat Who Is Always Hungry" By Lena D. - Juliana, Eva (Jurnal Hata Poda, 2024)
Phrase means a language unit that exists in one sentence function and consists of two or more terms. The research entitled "Analysis of the Use of Phrases in Short Story 'Kucing Yang Selalu Lapar' Karya Mas Kahfi" aims to identify the types of phrases, clauses, and sentences used in the short story. This research uses a qualitative descriptive method to collect and describe the data, which consists of various types of phrases found in the story. The researchers followed a read and write technique, where they first read thestoryandthenrecordedtheresultsoftheiranalysis.Thisstudyisuniqueinthatitfocuses specifically on analyzing the use of phrases, unlike previous studies that have only examined syntax in general. The researchers identified several types of phrases in the stories, including verbal phrases, numeral phrases, adverbial phrases, noun phrases, adjective phrases, and adjective phrases.This study aims to analyze the use of phrases in the short story "The Cat Who Is Always Hungry" by Lena D. The analysis focuses on identifying the types, structures, and functions of phrases used in the text, including noun phrases, verb phrases, adjective phrases, adverbial phrases, and prepositional phrases. Using a qualitative descriptive method, the data were collected through careful reading and annotation of the short story. The results show that Lena D. extensively uses noun and verb phrases to vividly describe characters and actions, while adverbial and prepositional phrases serve to enhance spatial and temporal settings in the narrative. The use of varied phrase structures contributes significantly to the expressive style and thematic depth of the story, creating a captivating and immersive reading experience. This research highlights the importance of phrase analysis in understanding an author's linguistic creativity and storytelling techniques.Keywords : phrases, syntax, short story, the always hungry cat.